Liquefaction evaluation method of coral sand: Case study on the ports in Indonesia - Ji, Zezhou; Ye, Xiangji; Zhang, Yingmin (Frontiers in Earth Science, 2023)
While the liquefaction evaluation methods of siliceous sand have undergone extensive studies, few research efforts were conducted to establish standard for the liquefaction susceptibility of coral sand. The current study develops an innovative method to evaluate the liquefaction potential of coral sand. Specifically, the method integrates the grain-size distribution of coral sand, effective overburden stress and equivalent seismic acceleration. Scanning electron microscopy image of coral sand was processed to reveal the microstructural characteristics of coral sand. The correction equation for standard penetration resistance of coral sand in Indonesian ports was given based on geotechnical investigations, and the recommended values of correction factors were proposed for the regions lacking relevant data in the previous period. The process for liquefaction evaluation method of coral sand was described and applied to evaluate the liquefaction potential of coral sand in Indonesian port projects. This study demonstrates the feasibility of integrating standard penetration test and grain-size distribution for liquefaction evaluation of coral sand.